Current State of Knowledge on the Orchids of Sarawak’s Peat Swamps. - Magdalina, Stephen; Almunah, Abd Mutalib; Meekiong, Kalu; Farah Alia, Nordin; Nur Haziah, Musa; Haniza, Razali; Mohd Akmal, Mohd Raffi (Sarawak Museum Department, 2022)
Sarawak’s peat swamp orchids are considered to be understudied, as most of the related research are favoured to the orchid species from mixed dipterocarp forests. Furthermore, distruptions of their natural habitat caused by various anthropogenic activities have made the orchid’s assessment studies, especially on the inventory and diversity, to be difficult. Consequently, it widens the knowledge gaps of the orchids’ natural history, current conservation status and their future in the peat swamp areas. Therefore, this inventory was conducted to compile and propose a provisional checklist of orchids distributed in the peat swamps of Sarawak. In total, 52 species from 26 genera of orchids were successfully compiled from the peat swamp areas located at lowlands and coastal plains of Betong, Bintulu, Kota Samarahan, Kuching, Limbang, Miri, Mukah, Sarikei, Sibu and Sri Aman districts. From the account, 10 species are endemic to Borneo. Current conservation status of the recorded species was assessed, and the significant roles of peat swamp areas as orchids natural habitat were further discussed. This compilation provides a glimpse on the current state of knowledge on the peat swamp orchids of Sarawak, thus serves as evidence to preserve the areas in their pristine conditions.